VARIASI GENETIK ANOPHELES SUNDAICUS BERDASARKAN SEGMEN ITS2 DNA RIBOSOM DAN GEN COI DNA MITOKONDRIA - Irfanul chakim (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
Entomological study with laboratory analysis done on Anopheles sundaicus mosquitoes as a malaria vector. The aim is to determine the existence of genetic variation in the Anopheles sundaicus species. PCR was used for the molecular identification of An. Sundaicus using COI and ITS2 genes. COI and ITS2 sequences in the study group compared with An. Epiroticus from GenBank. The comparation were done using a multiple sequence alignment program of Bioedit 7.1.9. The phylogenetic tree were constructed using neighbor-joining and bootstrap- tested by MEGA6. ITS2 sequence alignment results showed a single nucleotide substitution that can be used as markers for species determination. Phylogenetic tree analysis based on COI gene showed that An. Sundaicus in this study with isolates from GenBank, separate into two different groups or are polyphyletic. This study proved that An. Sundaicus from field collection was An. Epiroticus species by molecular identification. This study can be used to help public health policy related to vector control.Keywords: PCR, COI, ITS2, An. Sundaicus, An. Epiroticus